PE-Iv (Panorama Education-Italian version): the adaptation/validation of 5 scales, a step towards a SEL approach in Italian schools - Lynda S. Lattke; Aurelia De Lorenzo; Michele Settanni; Emanuela Rabaglietti (Frontiers in Psychology)
Implementing a Social and Emotional Learning (SEL) approach in school requires monitoring certain skills. As awareness of SEL increases in Italy, it is necessary to provide instruments to monitor these skills within a systemic approach. This study presents the cultural adaptation/validation of 5 scales from Panorama Education, which are widely used in school districts in the United States, to the Italian middle/high school context: Grit, Sense of Belonging, Self-Management, Social Awareness, and Self-Efficacy. After cultural adaptation, 709 middle/high school students answered an online questionnaire (2021). Psychometric properties showed good internal consistency and confirmatory factor analysis showed a good fit index. The differences in gender and grade level support the validity of the instrument.